2013
DOI: 10.1016/j.appet.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Intentional and inadvertent non-adherence in adult coeliac disease. A cross-sectional survey

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Appetite. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version was subsequently published in Appetite, 68, 2013Appetite, 68, , 10.1016Appetite, 68, /j.appet.2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 45 publications
9
92
1
Order By: Relevance
“…While these findings should be confirmed in further research, the relationship between gender and adherences indicates a potential need for additional support for men following a diagnosis of FBD. The findings for lifestyle impact and challenges accessing food are consistent with research in other areas which have found perceived barriers and selfefficacy to be important predictors of adherence (Clark-Cutaia, Ren, Hoffman, Burke, & Sevick, 2014;Hall, Rubin, & Charnock, 2013;Platt et al, 2014). Interventions that seek to reduce perceived barriers to adherence and improve self-efficacy may be successful in improving adherence in this population.…”
Section: Implications For Future Researchsupporting
confidence: 87%
“…While these findings should be confirmed in further research, the relationship between gender and adherences indicates a potential need for additional support for men following a diagnosis of FBD. The findings for lifestyle impact and challenges accessing food are consistent with research in other areas which have found perceived barriers and selfefficacy to be important predictors of adherence (Clark-Cutaia, Ren, Hoffman, Burke, & Sevick, 2014;Hall, Rubin, & Charnock, 2013;Platt et al, 2014). Interventions that seek to reduce perceived barriers to adherence and improve self-efficacy may be successful in improving adherence in this population.…”
Section: Implications For Future Researchsupporting
confidence: 87%
“…This specific hypothesis, as well as the broader question of directionality, requires testing. Intentional gluten consumption appears to be less common (Hall et al, 2009;Hall, Rubin, & Charnock, 2013). More high-quality research, using prospective and longitudinal designs, is needed to provide a more definitive answer to the question of causality.…”
Section: Discussionmentioning
confidence: 99%
“…Intentional gluten consumption in patients with CD appears rare, with unintentional non-adherence (e.g., due to cross contamination or errors in label reading) representing the most common reason for lapsing from the GFD (Hall, Rubin, & Charnock, 2013;Sainsbury et al, 2013a). Commonly used adherence measures, such as single-item self-report questions (e.g., 'how strictly do you adhere to your GFD?'…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to a GFD is difficult [Rashtak and Murray, 2012]. A recent study from the UK indicates that more than 70% of diagnosed CD patients consume gluten either intentionally or inadvertently [Hall et al 2013]. Furthermore, a GFD is not enough to suppress the disease or completely alleviate symptoms in a substantial number of patients .…”
Section: Introductionmentioning
confidence: 99%